A kind mind: effects of compassion-based meditation on prosocial intergroup outcomes in a South African pilot sample - Prevost, Adala M.; George, Michal; Fourie, Melike M. (Frontiers in Psychology, 2025)
Three decades into democracy, the corollaries of apartheid continue to pattern South African society, with complicated race feelings and resistance to reparative government policies still driving separation. Sharing a grounding with African knowledge systems in the interconnectedness of all people, compassion-based meditation has proven to be a powerful promoter of prosocial action toward strangers and stigmatized groups abroad. It is, however, unclear whether such findings would translate to South Africa with its history of racialised conflict. Here, we piloted a mixed methods study to examine whether 8 weeks of compassion-based meditation would foster positive intergroup attitudes and prosocial outcomes, beyond personal wellbeing, in a White South African sample. We found greater compassion self-practice to be associated not only with significantly increased life satisfaction and reduced stress, but also with heightened outgroup compassion and reduced desire for social distance. Furthermore, post intervention, we observed significantly reduced racial prejudice, increased intergroup contact, and greater prosocial outcomes expressed in support toward collective action and restitutive government policies. Qualitatively, participants reported broadened compassion and affiliation with strangers, suggesting enhanced self-transcendence. These findings offer early support for the potential of compassion-based meditation to improve intergroup relations locally. Future directions include a randomized controlled trial in an appropriately powered sample, and expansion of the methodology to include other social groups.